Beyond the genome: epigenetic regulation of immune responses and T cells in brain tumors - Sun, Shuo; Han, Yu; Li, Haiying; Wang, Chengyan; Zhou, Shu; Zhang, Xiaowei; Dai, Shuhong; Peng, Yao; Wang, Zhuoqun (Frontiers in Immunology, 2025)
Brain tumors such as glioblastoma remain among the most lethal and immunologically resistant cancers, in large part due to epigenetic programs that sculpt the tumor–immune microenvironment. DNA methylation, histone modifications, and chromatin remodeling do not merely drive tumor-intrinsic changes; they also profoundly reprogram immune responses, shaping antigen presentation, cytokine signaling, and immune cell recruitment. At the center of this regulation are T cells, whose effector functions are suppressed through promoter hypermethylation of antigen-processing genes, silencing of interferon pathways, and the establishment of exhaustion-specific chromatin states. Mutations such as IDH1/2 and H3K27M further reinforce these epigenetic barriers, fostering immune-cold microenvironments that disable cytotoxic T-cell activity. Emerging evidence highlights both CNS-specific adaptations, including microglial and astrocytic epigenetic programs that reinforce immune privilege, and conserved features of T cell exhaustion that mirror those in peripheral cancers. This duality underscores the need for therapeutic strategies that dismantle CNS-specific barriers while leveraging shared exhaustion programs across tumor types. Epigenetic drugs, ranging from DNA methyltransferase and EZH2 inhibitors to BET degraders and CRISPR-based epigenome editors, are beginning to restore antigenicity, reverse T cell dysfunction, and sensitize tumors to checkpoint blockade. Yet these approaches carry the paradoxical risk of disrupting CNS immune tolerance, potentially triggering harmful neuroinflammation or autoimmunity. To our knowledge, this is among the first comprehensive reviews to integrate CNS-specific immune privilege mechanisms with peripheral exhaustion pathways, providing a unified perspective on how epigenetic regulation orchestrates immune dysfunction across central and peripheral contexts. By mapping the continuum between immune evasion and global immunosuppression, we propose a conceptual framework for tailoring epigenetic-immunotherapy combinations to achieve durable antitumor immunity in the CNS.